Body Mass Index as a Determinant of Systemic Exposure to Gallotannin Metabolites during 6‐Week Consumption of Mango (Mangifera indica L.) and Modulation of Intestinal Microbiota in Lean and Obese Individuals. Issue 2 (28th November 2018) - Barnes, Ryan C.; Kim, Hyemee; Fang, Chuo; Bennett, William; Nemec, Matthew; Sirven, Maritza A.; Suchodolski, Jan S.; Deutz, Nicolaas; Britton, Robert A.; Mertens‐Talcott, Susanne U.; Talcott, Stephen T.
Abstract : Scope: This human clinical pilot trial investigated pharmacokinetics of gallotannin‐metabolites and modulation of intestinal microbiota in healthy lean and obese individuals after 6 weeks of daily mango consumption. Methods and results: Participants are divided into three groups: Lean Mango (LM: n = 12; BMI = 22.9 kg m −2 ), Obese Mango (OM: n = 9; BMI = 34.6 kg m −2 ), and Lean Control (LC: n = 11; BMI = 22.1 kg m −2 ). LM and OM consumed 400 g of mango per day for 6 weeks. LC consumed mango only on Days 0 and 42. After 6 weeks, LM experienced increased systemic exposure (AUC0–8h ) to gallotannin‐metabolites, 1.4‐fold ( p = 0.043). The greatest increase is 4‐ O ‐methyl‐gallic acid, 3.3‐fold ( p = 0.0026). Cumulative urinary excretion of gallotannin‐metabolites significantly increased in LM and OM, but not LC. For OM, qPCR data show increased levels of tannase‐producing Lactococcus lactis and decreased levels of Clostridium leptum and Bacteroides thetaiotaomicron, bacteria associated with obesity. LM experienced an increased trend of fecal levels of butyric (1.3‐fold; p = 0.09) and valeric acids (1.5‐fold; p = 0.056). Plasma endotoxins showed a decreased trend in LM and OM. Conclusion: Continuous mango intake significantly increased systemic exposure to gallotannin‐ metabolites and induced an increased trend for fecal short‐chain fatty acids in lean but not obese individuals. This pharmacokinetic discrepancy may result in BMI‐associated reduced gallotannin‐derived health benefits. Abstract : Continuous mango intake for 6 weeks increases systemic exposure to gallotannin metabolites and fecal short‐chain fatty acids in lean but not obese individuals. Obese individuals experience a trend toward increased tannase‐producing and decreased endotoxin‐producing bacteria levels. The lower systemic exposure to gallotannin metabolites in obese individuals may contribute to explaining the lack of efficacy of polyphenol‐rich treatments in human clinical trials with obese individuals.